Effective Technical Defense and Judicial Role - Feldens, Luciano (2024)
Only a defense that is widely assured and diligently executed can be qualified as legally effective (art. 5, LV, of the CF). That said, there are two direct threats that can impact the due right to defense: (i) the State, which, through its agents, may promote illegitimate restrictions on defense (restricted defense); (ii) the lawyers, who may deliver deficient and/or mediocre work, i.e. below what is required by the standards of professional conduct and the circumstances of the case. In any such situation, the Judiciary has the duty to safeguard the right to effective defense, guaranteeing that it is duly enforced either by removing any obstacles imposed to the exercise of the right, or by effectively ensuring that the conditions for its exercise are present.